IMPLEMENTASI METODE IQRO’ DALAM MENGATASI MASALAH KESULITAN MEMBACA AL-QUR’AN SISWA MTS NU TMI PUJON KABUPATEN MALANG - Nurrohmatul Fidhyah; Arna Ulinnuha; Rachmad Arif Ma'ruf (Muróbbî: Jurnal Ilmu Pendidikan, 2022)
The Qur’an is a way of life for every Muslim, where the Qur’an is the source of all knowledge. Al-Qur’an has a language that is different from everyday language, because of it, the process of learning the Qur’an from an early age is very necessary to be able to read the Qur’an well and correctly. However, today there are still many children have not been able to read the Qur’an well, because many people are more concerned with general science than the science of the Qur’an.This study aims to  find out the implementation of the Iqro’ method to solving problem the difficulty of reading al-Qur’an students of MTs NU TMI Pujon. This research use descriptive qualitative approach with a case study. Data collection techniques used were observation, interviews, and documentation.The results showed that 1) Difficulties in reading al-Qur’an students include: difficulty in pronouncing letters according to their makhorijul huruf, short lengths of reading, upside down in mentioning hijaiyah letters, and not being able to read conjunctions. 2) The implementation of the iqro method 'that is just before the Teaching and Learning Activity starts precisely at 06:30 to 07:00. 3) Obstacles experienced by the process of implementing the iqro method are a lack of teaching staff (so assisted by a some of students to help the implementation of the iqro method) and lack of time.